Photocatalytic Degradation of Methylene Blue under UV Light Irradiation on Prepared Carbonaceous TiO2 - Zatil Amali Che Ramli; Nilofar Asim; Wan N. R. W. Isahak; Zeynab Emdadi; Norasikin Ahmad-Ludin; M. Ambar Yarmo; K. Sopian (The Scientific World Journal)
This study involves the investigation of altering the photocatalytic activity of TiO2 using composite materials. Three different forms of modified TiO2, namely, TiO2/activated carbon (AC), TiO2/carbon (C), and TiO2/PANi, were compared. The TiO2/carbon composite was obtained by pyrolysis of TiO2/PANi prepared by in situ polymerization method, while the TiO2/activated carbon (TiO2/AC) was obtained after treating TiO2/carbon with 1.0 M KOH solution, followed by calcination at a temperature of 450°C. X-ray powder diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared (FTIR), thermogravimetric analysis (TG-DTA), Brunauer-Emmet-Teller (BET), and UV-Vis spectroscopy were used to characterize and evaluate the prepared samples. The specific surface area was determined to be in the following order: TiO2/AC > TiO2/C > TiO2/PANi > TiO2 (179 > 134 > 54 > 9 m2 g−1). The evaluation of photocatalytic performance for the degradation of methylene blue under UV light irradiation was also of the same order, with 98 > 84.7 > 69% conversion rate, which is likely to be attributed to the porosity and synergistic effect in the prepared samples.